The Role of Grit in Organizational Performance During a Pandemic - Lee, Joonghak (Frontiers in Psychology, 2022)
In the context of the organizational crisis caused by COVID-19, scholars and professionals have focused on factors that help employees stay at their jobs and perform well. In an uncertain era, grit is a significant employee and organizational sustainability trait. Using 890 responses, this study determined how grit affects organizational performance and used contingencies including supportive climate and transformational leadership as moderators. The hypotheses were tested by examining the relationship between grit and organizational performance and the moderating effects of supportive climate and transformational leadership. Further, these hypotheses were supported by confirmatory factor analysis, PROCESS macro analysis, and bootstrapping. Grit was found to be positively associated with organizational performance; meanwhile, supportive climate and transformational leadership strengthen the relationship between grit and performance. Both theoretical and practical implications of the findings are discussed. This study makes a theoretical contribution through its assessment of the impact of grit on organizational performance. Trait activation theory can explain how grit can be expressed through organizational climate and leadership. With regard to practice, grit can be used as a vital factor for personnel selection and a supportive climate should be provided to ensure a desirable organizational climate.